Reduction of GTP Cyclohydrolase I Feedback Regulating Protein Expression by Hydrogen Peroxide in Vascular Endothelial Cells - Masakazu Ishii; Shunichi Shimizu; Teruaki Wajima; Tamio Hagiwara; Takaharu Negoro; Akira Miyazaki; Takashi Tobe; Yuji Kiuchi (Elsevier, 2005)
We examined the effect of H2O2 on the expression of GTP cyclohydrolase I (GTPCH) feedback regulating protein (GFRP). Addition of H2O2 to endothelial cells decreased GFRP mRNA levels, in contrast to the increase of tetrahydrobiopterin (BH4) content and GTPCH mRNA levels. The inhibitors of nitric oxide (NO) synthase and GTPCH had no influence on the decrease of GFRP mRNA levels in H2O2-treated cells. It is suggested that H2O2 induces BH4 synthesis through not only induction of GTPCH but also reduction of GFRP. The decrease of GFRP mRNA level appears to be independent of the produced NO and BH4. Keywords:: GTP cyclohydrolase I, GTP cyclohydrolase I feedback regulating protein, hydrogen peroxide